Slashed and burned: war, environment, and resource insecurity in West Borneo during the late nineteenth and early twentieth centuries - Wadley, R.L. (2007)
European colonial efforts to pacify ‘rebellious’ Iban in western Borneo during the late nineteenth and early twentieth centuries produced chronic resource insecurity and may have contributed to the recorded destructiveness of Iban swidden cultivation. Negative European opinions towards swiddening may have thus been reinforced by a context that the Europeans themselves created. Drawing on anthropological theories linking swidden cultivation and Iban warfare, this article presents a historical case for the relationship between pacification, resource insecurity, and swidden destructiveness. It also re-evaluates Derek Freeman’s original diagnosis of Iban as ‘prodigal’ farmers, suggesting that there may have been more to Iban pioneering destruction than the wide availability of ‘virgin’ forest.